The The Relationship between the Use of Interactive Digital Media in Civic Education Learning and Students' Learning Motivation - Hayati, Lutfiah Isfa; Sih Dewanti, Sintha (Universitas Pendidikan Ganesha, 2025)
Learning motivation plays a crucial role in elementary education, supporting both the achievement of learning objectives and the enhancement of students’ abilities. However, in practice, many students still exhibit low motivation despite the use of interactive digital media in the learning process. This study aims to analyze the relationship between the use of interactive digital media in Civic Education and the learning motivation of elementary school students. A quantitative correlational design was employed with 80 fourth-grade students selected purposively. Data were collected using a validated and reliable Likert-scale questionnaire, then analyzed with descriptive statistics and Pearson’s correlation test. The findings revealed that although both the intensity of digital media use and students’ learning motivation were categorized as high, no significant relationship was found between them (r = 0.100; p = 0.378). These results suggest that interactive digital media alone does not directly enhance learning motivation without the integration of participatory and contextual teaching strategies. This study highlights the importance of combining digital media with pedagogical approaches that actively involve students to optimize motivation in Civic Education learning. The implication is that interactive digital media should not be viewed as an independent solution, but rather as a complementary tool that requires alignment with participatory strategies. Such integration is essential to maximize its effectiveness in fostering learning motivation among elementary school students.